Evaluasi Aplikasi Pemantauan Berkas untuk Modernisasi Layanan dan Penerbitan Dokumen Elektronik di Bidang Pertanahan - Az-zahra, Salsabilla; Nugroho, Tanjung; Arnanto, Ardhi; Wahyuni, Wahyuni (Widya Bhumi, 2025)
The digital transformation of land services still faces challenges, such as weak file monitoring, lost documents, and the accumulation of backlogs among officers. This study aims to evaluate the SIAMEL (Electronic Media Transfer System) application for modernizing services and issuing electronic documents in the land sector. This study used a mixed-methods approach with primary and secondary data collection. Qualitative data were obtained through structured interviews, participant observation, and document studies, while quantitative data were collected through a questionnaire-based survey and SIAMEL application performance testing using Webpage Test. Analysis was conducted descriptively and experimentally to evaluate SIAMEL's effectiveness in improving the accuracy, efficiency, and transparency of land services. The results indicated that SIAMEL improves operational transparency and accountability through digital audit trails, real-time searches, and a backlog dashboard that generates objective metrics (work volume, average completion time, and backlog level per officer). Technical evidence supports operational feasibility through very fast server response (TTFB = 0.123 s), maintained interface stability (CLS/TBT ≈ 0), and high bandwidth efficiency (page weight decreased ≈ 98.9% on repeat view). In conclusion, SIAMEL has been proven to be effective in supporting the modernization of land services through document digitization. This study emphasizes the importance of adopting file monitoring systems in other government agencies as a strategic step in creating good public services. Keywords: File Monitoring, Performance, Media Transfer, Electronic Land Certificates   Transformasi digital layanan pertanahan masih menghadapi tantangan, seperti lemahnya pengawasan perjalanan berkas, kehilangan dokumen, dan akumulasi tunggakan berkas pekerjaan antar petugas. Penelitian ini bertujuan untuk mengevaluasi aplikasi SIAMEL (Sistem Alih Media Elektronik) untuk modernisasi layanan dan penerbitan dokumen elektronik di bidang pertanahan. Penelitian ini menggunakan mixed-methods dengan pengumpulan data primer dan sekunder. Data kualitatif diperoleh melalui wawancara terstruktur, observasi partisipatif, dan studi dokumen, sedangkan data kuantitatif dikumpulkan melalui survei berbasis kuesioner dan pengujian performa aplikasi SIAMEL menggunakan WebPageTest. Analisis dilakukan secara deskriptif dan eksperimental untuk mengevaluasi efektivitas SIAMEL dalam meningkatkan akurasi, efisiensi, dan transparansi layanan pertanahan. Hasil penelitian menunjukkan bahwa SIAMEL meningkatkan transparansi dan akuntabilitas operasional melalui audit-trail digital, pencarian real-time, serta dashboard klasemen tunggakan yang menghasilkan metrik objektif (volume kerja, waktu penyelesaian rata-rata, tingkat tunggakan per petugas). Bukti teknis mendukung kelayakan operasional melalui respons server sangat cepat (TTFB = 0,123 s), stabilitas antarmuka terjaga (CLS/TBT ≈ 0), dan efisiensi bandwidth tinggi (page weight turun ≈ 98,9% pada repeat view). Kesimpulannya, SIAMEL terbukti efektif mendukung modernisasi layanan pertanahan melalui digitalisasi dokumen. Penelitian ini menekankan pentingnya adopsi sistem pemantauan berkas di instansi pemerintah lain sebagai langkah strategis terciptanya pelayanan publik yang baik.